2014
DOI: 10.1590/s0100-69162014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Demanda tractiva en función de la resistencia mecánica del suelo a la penetración

Abstract: RESUMO:No presente estudo, foram elaborados modelos empíricos para determinar a força de tração demandada por arados de discos, escarificadores e semeadoras adubadoras, em função da resistência mecânica do solo à penetração. A média da referida resistência, determinou-se até as profundidades de 25; 35 e 15 cm, em correspondência com as regulagens do arado de discos, escarificador e semeadora adubadora. O ajuste foi verificado de acordo com o coeficiente de determinação, gráficos de dispersão, análise residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The normality of residuals of the neural networks with the best indexes was assessed using the Kolmogorov-Smirnov, Lilliefors, and Shapiro-Wilk tests, and the adjustment between the observed and estimated values was confirmed using the Student's t-test, as suggested by Borges et al (2017). Moreover, taking as reference the studies of Although the presented analytical criteria confirmed the accuracy of the networks in predicting the THI, Borges et al (2014Borges et al ( , 2017 recommend graphically evaluating the characteristics of the residuals to assess the presence of inadequate trends in their distribution. For this purpose, different graphs should be prepared, including the histogram of residuals, a quantile-quantile plot with confidence intervals, a graph with the values of the residuals as a function of the estimated values, a graph with the values of the residuals according to the day of the year (independent variable), and a scatter plot with the observed values and values estimated by each selected network for each day of the year.…”
Section: Methodsmentioning
confidence: 73%
“…The normality of residuals of the neural networks with the best indexes was assessed using the Kolmogorov-Smirnov, Lilliefors, and Shapiro-Wilk tests, and the adjustment between the observed and estimated values was confirmed using the Student's t-test, as suggested by Borges et al (2017). Moreover, taking as reference the studies of Although the presented analytical criteria confirmed the accuracy of the networks in predicting the THI, Borges et al (2014Borges et al ( , 2017 recommend graphically evaluating the characteristics of the residuals to assess the presence of inadequate trends in their distribution. For this purpose, different graphs should be prepared, including the histogram of residuals, a quantile-quantile plot with confidence intervals, a graph with the values of the residuals as a function of the estimated values, a graph with the values of the residuals according to the day of the year (independent variable), and a scatter plot with the observed values and values estimated by each selected network for each day of the year.…”
Section: Methodsmentioning
confidence: 73%
“…Moreover, taking as reference the studies of Binoti et al (2014a, b), Georgens et al (2014), Soares et al (2014), and Borges et al (2017), the correlation coefficients (r), Willmott's index of agreement (Iw), and performance index (Id) were calculated, and the latter index measures the proximity between the observed and estimated values. Dai et al (2014), Rodrigues et al (2015), Sousa et al (2015), Brighenti et al (2016), Chaves et al (2016), Lopes et al (2016), andMachado et al (2017) recommend evaluating the efficiency of the networks using the Nash-Sutcliffe coefficient (NSC) (Nash & Sutcliffe, 1970) according to equation: Although the presented analytical criteria confirmed the accuracy of the networks in predicting the THI, Borges et al (2014Borges et al ( , 2017 recommend graphically evaluating the characteristics of the residuals to assess the presence of inadequate trends in their distribution. For this purpose, different graphs should be prepared, including the histogram of residuals, a quantile-quantile plot with confidence intervals, a graph with the values of the residuals as a function of the estimated values, a graph with the values of the residuals according to the day of the year (independent variable), and a scatter plot with the observed values and values estimated by each selected network for each day of the year.…”
Section: Methodsmentioning
confidence: 99%